Capsid Protein C of Tick-Borne Encephalitis Virus Tolerates Large Internal Deletions and Is a Favorable Target for Attenuation of Virulence - Kofler, Regina M. (American Society for Microbiology, 2002)
Deletions ranging in size from 4 to 21 amino acid residues were introduced into the capsid protein of the flavivirus tick-borne encephalitis (TBE) virus. These deletions incrementally affected a hydrophobic domain which is present at the center of all flavivirus capsid protein sequences and part of which may form an amphipathic alpha-helix. In the context of the full-length TBE genome, the deletions did not measurably affect protein expression and up to a deletion length of 16 amino acid residues, corresponding to almost 17% of mature protein C, viable virus was recovered. This virus was strongly attenuated but highly immunogenic in adult mice, revealing capsid protein C as a new and attractive target for the directed attenuation of flaviviruses. Apparently, the larger deletions interfered with the correct assembly of infectious virus particles, and this disturbance of virion assembly is likely to be the molecular basis of attenuation. However, all of the mutants carrying large deletions produced substantial amounts of subviral particles, which as judged from density gradient analyses were identical to recombinant subviral particles as obtained by the expression of the surface proteins prM and E alone. The structural and functional flexibility of protein C revealed in this study and its predicted largely alpha-helical conformation are reminiscent of capsid proteins of other enveloped viruses, such as alphaviruses (N-terminal domain of the capsid protein), retroviruses, and hepadnaviruses and suggest that all of these may belong to a common structural class, which is fundamentally distinct from the classical β-barrel structures of many icosahedral viral capsids. The possibility of attenuating flaviviruses by disturbing virus assembly and favoring the production of noninfectious but highly immunogenic subviral particles opens up a promising new avenue for the development of live flavivirus vaccines.